Contact a novel - Sagan, Carl 1934-1996 (Simon and Schuster, 1985)
Beautiful astrophysicist Rebecca Blake deciphers long-awaited signals from space, persuades world leaders to construct a machine that many consider a Trojan Horse, and journeys into space for an epochal encounter.
Keywords: Interstellar communication -- Fiction; Life on other planets -- Fiction; Radio astronomy -- Fiction; Science fiction.; Women scientists -- Fiction; Science fiction